2021
DOI: 10.1002/cam4.4023
|View full text |Cite
|
Sign up to set email alerts
|

Preinfection laboratory parameters may predict COVID‐19 severity in tumor patients

Abstract: Background Infection with SARS‐CoV‐2 leads to COVID‐19, the course of which is highly variable and depends on numerous patient‐specific risk factors. Patients with tumor diseases are considered to be more susceptible to severe COVID‐19; however, they also represent a heterogeneous group of individuals with variable risk. Identifying specific risk factors for a severe course of COVID‐19 in patients with cancer is of great importance. Methods Patients diagnosed with solid tumors or hematological malignancies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(113 reference statements)
0
2
1
Order By: Relevance
“…In our series we could not find any correlation between clinical severity or overall survival after COVID-19 associated to changes in absolute counts of neutrophils. Differently from data obtained from the general population or in cancer patients, the pre-infection absolute count of neutrophils and lymphocytes, C-RP and LDH were not associated to OS in unvaccinated patients included in our series [ 36 , 46 ]. However, C-RP and LDH were higher in those patients who did not achieve viral clearance by 14 days, reflecting the impairment of the inflammatory status in COVID-19 [ 50 ].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In our series we could not find any correlation between clinical severity or overall survival after COVID-19 associated to changes in absolute counts of neutrophils. Differently from data obtained from the general population or in cancer patients, the pre-infection absolute count of neutrophils and lymphocytes, C-RP and LDH were not associated to OS in unvaccinated patients included in our series [ 36 , 46 ]. However, C-RP and LDH were higher in those patients who did not achieve viral clearance by 14 days, reflecting the impairment of the inflammatory status in COVID-19 [ 50 ].…”
Section: Discussioncontrasting
confidence: 93%
“…There were no significant differences in pre-infection laboratory parameters evaluated among unvaccinated and fully vaccinated patients, including absolute counts of neutrophils, monocytes and lymphocytes, C-reactive protein (C-RP) and lactate de-hydrogenase, which have been associated with COVID-19 severity in both general population and cancer subjects [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are enhanced by the knowledge that neutrophilia has been described as an indicator of severe respiratory symptoms and a poor outcome in the novel coronavirus disease that was first identified in 2019 (COVID-19) [149][150][151][152]. It has been observed that neutrophil count in the circulation was the greatest independent prognostic indicator for COVID-19 mortality [153], highlighting the importance of neutrophils in viral infections and the prognostic potential for neutrophils in COVID-19, which also has implications for treatment courses.…”
Section: Detrimental Potential Of Different Neutrophil Subsets and Th...mentioning
confidence: 96%